Pantaleoni's Problem in the Oscillation of Prices - Moore, Henry Ludwell (Quarterly Journal of Economics, 1926)
Simple and complex demand functions, 587. — An index number of oscillations of most probable prices, 591. — Price oscillations in relation to partial flexibilities of prices, 592. — A clue to periodic oscillations or cycles, 593. — Conclusions, 594.